Augmented reality in medical education: a systematic review - Kevin S. Tang (Canadian Medical Education Journal, 2020)
Introduction: The field of augmented reality (AR) is rapidly growing with many new potential applications in medical education. This systematic review investigated the current state of augmented reality applications (ARAs) and developed an analytical model to guide future research in assessing ARAs as teaching tools in medical education.